Hydrothermal Preparation of Photoluminescent Graphene Quantum Dots Characterized Excitation‐Independent Emission and its Application as a Bioimaging Reagent. (10th March 2014) - Zhu, Xiaohua; Xiao, Xin; Zuo, Xiaoxi; Liang, Yong; Nan, Junmin
<x xml:space="preserve">Abstract</x> Zero‐dimensional photoluminescent (PL) graphene quantum dots (GQDs) that can be used as the cell‐imaging reagent are prepared by a hydrothermal route using the graphene oxide (GO) as the carbon source. Under the optimized hydrothermal conditions, an initial hydrogen peroxide concentration of 0.5 mg mL−1 at 180 °C for 120 min, the GO sheets can be cut into nanocrystals with lateral dimensions in the range of 1.5–5.5 nm and an average thickness of around 1.1 nm. The as‐prepared GQDs exhibit an abundance of hydrophilic hydroxy and carboxyl groups and emit bright blue luminescence with up‐conversion properties in a water solution at neutral pH. Most interestingly, they indicate excitation‐independent emission characteristics, and the surface state is demonstrated to have a key role in the PL properties. The fluorescence quantum yield of the GQDs is tested to be around 6.99% using quinine sulfate as a standard. In addition, the as‐prepared GQDs can enter into HeLa cells easily as a fluorescent imaging reagent without any further functionalization, indicating they are aqueous stability, biocompatibility, and promising for potential applications in biolabeling and solution state optoelectronics.